Parallel strategies on a distributed parallel computer system - Alias, Norma (Universiti Teknologi Malaysia, 2004)
The formulation of a new parallel iteration methods are created to solve the parabolic equations in one, two and three dimensions run on a distributed parallel computer systems on the homogeneous parallel machines with 20 PC Intel Pentium IV, speed 1.6MHz and with PVM application platform. The development of IADE class and AGE with (4,2) and (2,2) accuracies are oriented by ADI algorithm with time level splitting strategy by an alternating way. The alternative iterative method for IADE and AGE classes is created. There are IADEI method which is based on Richardson's formula and AGE_BRIAN which is based on linear interpolation concept. The development of a few strategies parallel is being as a mechanism for IADE to make it implemented in parallel. The Comparisons of the sequential performance measurements in IADE class with SUB, SOR, RB, MULTI, VECTOR and MF strategies are implicated the higher convergent and accuracy of IADEB-SUB and IADE-SUB methods. The Comparisons of the parallel performance measurements for IADE and AGE classes shown the elements of AGE class such as the overlapping subdomain and implicit block (2X2) are implicated the speedup and efficiency of AGE class is higher than IADE class. the minimum of the cost communication for the AGE class compared to IADEB-SUB and IADE-SUB are proved that AGE class is compatibility implemented on distributed parallel computer systems. The Expansion of AGE class on one, two and three dimensions for Cartesian, cylindrical and spherical coordinate systems make a decision that AGE-BRIAN methods is an alternative for AGE class in terms of convergent, accuracy, time executions, speedup, efficiency, effectiveness and temporal performance Communication activities and the consistent and work balance of data decomposition technique for CG method compatibility of the distributed parallel computer systems barriers.